AC dielectrophoretic deformable particle‐particle interactions and their relative motions. Issue 10 (25th September 2019) - Zhou, Teng; Ji, Xiang; Shi, Liuyong; Zhang, Xianman; Song, Yongxin; Joo, Sang Woo
Abstract: This paper develops a numerical simulation model to research the deformable particle‐particle interactions caused by dielectrophoresis (DEP) under AC electric fields. The DEP force is calculated by using Maxwell stress tensor method, and the hydrodynamic force is obtained by calculating the hydrodynamic stress tensor. Simulation results show that the DEP interactive motion will facilitate the particles forming particle chains that are parallel to the electric field, and the particles with low shear modulus present a lower x‐component velocity. Also, the electric field intensity and particles radius have some effects on the DEP motions, and for different particles, smaller particles with larger electric field intensity easily reach a larger velocity. The numerical research may provide universal guidance for biological cells manipulation and assembly.